Perspektif Negara Komunis Menyoroti Tren Etika dan Pendidikan Komparatif - Rojak, Abdul; Sauri, R Supyan; Saputra, Wahyu Rananda; Sutisna, Syarip Hidayat (AHKAM, 2023)
In this article, I have tried to highlight some aspects of the two perspectives. The first is the perspective of the researcher who recalls his past as a student in a communist country, interpreting his life experiences given his impact on his education and teaching profession. The second perspective is that of the researcher who looks to the future, initially lacking in resources but willing to connect with global research in his area of interest, educational ethics. International studies that support and inspire our research in the domain of educational ethics include philosophical works, the study of moral psychology, and resources from sociology and organizational psychology as well as from pedagogy. Regarding expected trends in comparative and international education, I have grouped them into three categories: (1) Trends related to research themes in comparative education: many of the main themes of education have been filtered or will be filtered through a comparative lens (educational history, philosophy- educational physics, curriculum and didactics, sociology of education, politics and economics of education and educational psychology); (2) Methodological trends in quantitative and qualitative methodologies together will support the research process in comparative education; and (3) Trends regarding the impact of research in comparative pedagogy: Global Models of will Inspire Local Initiatives without Copiable Beings.